Sustainability and corporate mechanisms in Asia / Ernest Lim. - Lim, Ernest, 1977- (International corporate law and financial market regulation., 2020)
This is the first book to provide a comparative and critical analysis of why and how six corporate mechanisms - (1) sustainability reporting; (2) board gender diversity; (3) constituency directors; (4) stewardship codes; (5) directors' duty to act in the company's best interests; and (6) liability on companies, shareholders and directors - have been or can be used to promote sustainability in the four leading common law jurisdictions in Asia (Singapore, Hong Kong, India and Malaysia). A central challenge is, whether and if so, how the corporate mechanisms should be reconceptualised to promote sustainability in an environment that is characterised by controlling shareholders, particularly the government in state-owned enterprises. Because controlling shareholders are the norm for the majority of the world's companies, and state-owned enterprises play a significant role, this book has important insights on the problems and prospects of advancing sustainability in concentrated and mixed ownership jurisdictions.